2021
DOI: 10.1007/s10462-021-10029-9
|View full text |Cite
|
Sign up to set email alerts
|

An extended hesitant fuzzy set using SWARA-MULTIMOORA approach to adapt online education for the control of the pandemic spread of COVID-19 in higher education institutions

Abstract: The world has been challenged since late 2019 by COVID-19. Higher education institutions have faced various challenges in adapting online education to control the pandemic spread of COVID-19. The present study aims to conduct a survey study through the interview and scrutinizing the literature to find the key challenges. Subsequently, an integrated MCDM framework, including Stepwise Weight Assessment Ratio Analysis (SWARA) and Multiple Objective Optimization based on Ratio Analysis plus Full Multiplicative For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 49 publications
0
22
0
Order By: Relevance
“…Cui et al ( 2021 ) combined Pythagorean fuzzy SWARA with the combined compromise solution (CoCoSo) method in order to IoT adaption barriers for the circular economy. Recently, Saraji et al ( 2021 ) suggested an integrated decision-making framework by combining SWARA and multi-objective optimization based on ratio analysis with the full multiplicative form (MULTIMOORA) with hesitant fuzzy sets (HFSs) and applied to adapt online education during COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Cui et al ( 2021 ) combined Pythagorean fuzzy SWARA with the combined compromise solution (CoCoSo) method in order to IoT adaption barriers for the circular economy. Recently, Saraji et al ( 2021 ) suggested an integrated decision-making framework by combining SWARA and multi-objective optimization based on ratio analysis with the full multiplicative form (MULTIMOORA) with hesitant fuzzy sets (HFSs) and applied to adapt online education during COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Saraji et al [ 29 ] offered the MCDM problem to select suitable education techniques under hesitant fuzzy sets. Alkan and Kahraman [ 30 ] introduced IF-TOPSIS method to choose the hospital site under pandemic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The coronavirus disease 2019 (COVID-19) outbreak has adversely affected all social sectors worldwide, including the economy, healthcare, and education (1)(2)(3)(4)(5). Its high infectivity has necessitated measures such as social distancing, isolation, and travel restrictions, bringing almost all face-to-face activities to a standstill (1,4,6).…”
Section: Introductionmentioning
confidence: 99%